Secular morality and the university - Emmanuel S. de Dios (University of the Philippines, School of Economics (UPSE), 2008)
Secular morality is implied in the University's very founding, with roots dating back to the 18th century Enlightenment that informed both the defeated Philippine revolution and the political ideas of the American occupiers. Citing recent knowledge gained from behavioural games and evolutionary psychology, this paper discusses how a public morality that is secular, minimal, and libertarian, is both possible and desirable in a complex society. The paper then illustrates how such a morality can inform politics and public policy in such difficult issues as illegal gambling, contraception and abortion, and living-organ donation. The state university's role in developing and strengthening the idea of secular morality is then discussed.
Keywords: 330